The Resurgence of Religion : A Comparative Study of Selected Themes in Christian and Islamic Fundamentalist Discourses - Zeidan, David. (Numen Book Series, 2003)
This book is a comparative study of basic themes in Christian and Islamic fundamentalist discourses, analyzing and comparing texts from a wide variety of fundamentalist leaders and movements, looking for \'family resemblances\' and significant differences in order to better understand the contemporary phenomenon of religious resurgence. After placing fundamentalisms in a theoretical framework, the study looks at selected themes important to fundamentalists, noting resemblances and differences. These themes include their anti-secularist stance, their theocentric worldviews, their reliance on inerrant sacred scriptures, and their attitudes to politics, government, state and democracy. The study also looks at the fundamentalist view of the world as a perennial battlefield between the forces of good and those of evil, in the realm of ideologies as well as politics and the legitimation of violence.